Recognizing states international society and the establishment of new states since 1776 - Fabry, Mikulas (Oxford University Press, 2010)
This book examines recognition of new states, the practice historically employed to regulate membership in international society. The last twenty years have witnessed new or lingering demands for statehood in different areas of the world. The claims of some, like those of Bosnia and Herzegovina, Eritrea, Croatia, Georgia and East Timor, have achieved general recognition; those of others, like Kosovo, Tamil Eelam, South Ossetia, Abkhazia and Somaliland, have not. However, even asmost of these claims gave rise to major conflicts and international controversies, the criteria for acknowledgment of
Keywords: Geschichte 1776-2005; State succession : History; Recognition (International law) : History; Legitimacy of governments; Self-determination, National